Aproveitamento de água da chuva para fins não potáveis - Silva, Osvaldo Soares da (2015)
The research aimed to present the possible use of tanks in urban homes with rainwater harvesting for non-potable purposes. Together with the proposal presents the laws that support and encourage the creation and applicability of alternative techniques for decompression of water resources, in order to maintain and guarantee the quality and quantity of water for future generations. The research addresses the question as improper use of wastewater, and the possibility of introducing the possible use of tanks in urban homes. For the development of research were carried out review of the relevant literature that demonstrated the economic feasibility of the use of tanks to capture rainwater, thus avoiding the consumption of noble water for domestic uses that do not require the quality of drinking water. Questions regarding the preservation of water resources are raised with awareness of the use of drinking water for purposes other than watering every day. In the face of rainwater utilization techniques in urban homes, are sustainable solutions that contribute to the rational use of water, taking advantage of the potential rainfall of townhouses, with a view to the preservation of water resources. Analyzed the economic potential that the use of rainwater for non-potable consumption in urban households can offer, explaining the process of capture and storage, through a utilization system for best use of this resource, which is economically viable and social reach. On the availability of alternative funding, such water can be used to irrigate gardens, wash sidewalks and even in the sanitary basin where the water consumption can be quite high. Many problems in the area of water resources present in Brazil, as occurrence of periodic flooding in the rainiest periods; water shortages in places with low intensity rainfall; lack of government efficient practices; ignorance of the benefits of rainwater utilization by the population. In Brazil, the only law that establishes some criteria for rainwater harvesting is the NBR 15527, but not mandatory basis, taking only the adjustments to the national reality through studies on the specific conditions of each region and the potential risks that might bring to human health.